Transformational Leadership in the Perspective of Islamic Education: A Comparative Analysis of Al-Ghazali's Thought and Modern Leadership Theory - Sita Arum Damayanti; Faqih Abdul Aziz; Iffatut Tazkiyyah (ADARA, 2025)
Leadership in Islamic educational institutions continuously faces a critical dichotomy between the relentless demands of modern, secular transformational management and the imperative to preserve classical religious values. This study aims to comparatively analyze the epistemological and ontological foundations of Al-Ghazali’s leadership thought and modern transformational leadership theory to construct an integrative synthesis. Employing a qualitative library research method with a historical-philosophical and comparative approach, this study extracts conceptual data from Al-Ghazali’s classical texts alongside foundational theories developed by Burns and Bass. The results reveal a profound paradigmatic contrast: transformational leadership operates on a positivistic, anthropocentric epistemology focused exclusively on observable organizational behaviors (the Four I's), whereas Al-Ghazali’s framework relies on a theocentric (Tawhid) foundation emphasizing internal moral character. To resolve this dichotomy, this study constructs the "Transformational-Ghazalian Leadership Model". In this novel framework, Al-Ghazali’s four cardinal virtues (Hikmah, Syaja'ah, Iffah, 'Adl) serve as the inner spiritual core that strictly guides and purifies the external operationalization of transformational behaviors. Consequently, idealized influence is rooted in iffah, inspirational motivation in syaja'ah, intellectual stimulation in hikmah, and individualized consideration in 'adl. This integrative synthesis provides a critical theoretical breakthrough, legitimizing modern organizational changes within Islamic institutions without compromising their eschatological objectives (falah). Future research is highly recommended to empirically validate this conceptual model through quantitative or mixed-methods assessments across various Islamic educational institutions.